Zarządzanie talentami - Pochopień, Jolanta (Zeszyty Naukowe SGGW - Ekonomika i Organizacja Gospodarki Żywnościowej, 2011)
Talent management is listed as the world’s major trends. The author presents the causes of the growing importance of talents in companies, acquisition methods, development and a new pattern of talent management: “talent on demand” model which is more appropriate for 21st century business. The author also points out the possibility of using analitycal tools in talent management. The article presents the study results of talent management.